Pharmacokinetics, Pharmacodynamics, Safety, Tolerability, and Immunogenicity of the QX002N anti-IL-17 Monoclonal Antibody: A Phase I, Randomized, Double-Blind, Single Ascending Dose Study in Healthy Chinese Volunteers - Wu, Min; Zhang, Hong; Li, Qianqian; Chen, Hong; Fang, Min; Yang, Lizhi; Ding, Yanhua (Frontiers in Pharmacology, 2022)
Background: The innovative injection of interleukin 17 A (IL-17A) monoclonal antibody QX002N is being developed to treat active ankylosing spondylitis and plaque psoriasis in adults. Objective: This study investigated the pharmacokinetics (PKs), pharmacodynamics (PDs) safety, tolerability, and immunogenicity of single ascending subcutaneous injections of QX002N in healthy Chinese volunteers. Methods: A total of 65 healthy subjects were enrolled in a randomized, double-blind, placebo-controlled, single ascending dose phase I study (10–320 mg). Ten subjects were allocated to each cohort (containing 8 subjects treated with QX002N and 2 with placebo), except cohort 1 (only 4 subjects treated with QX002N and 1 with placebo). The studies on PKs, PDs, tolerability, and immunogenicity of QX002N were performed. Results: Our study showed that QX002N injection was well tolerated, without deaths, serious adverse events, or discontinuations due to treatment-emergent adverse events (TEAEs). Neither more frequency nor high severity of the drug-related adverse reaction was observed with increasing QX002N dose. The TEAEs in all subjects were considered Grades 1–2 (CTCAE 5.0) except for one case of Grade 3 (hypertriglyceridemia). Tmax of QX002N was obtained from 168 to 240 h across the dose range after administration. The Cmax and area under the curve of QX002N increased in proportion to dose, and showed linear PKs. Anti-drug antibody positivity was detected in one (1.9%) subject after drug administration. Conclusion: QX002N was well tolerated in our study. Based on the PKs and safety results of QX002N, 80 mg is recommended as the effective dose for a future phase Ib study. Clinical Trial Registration: https://www.chinadrugtrials.org.cn/, identifier ChiCTR1900023040.